UPAYA PENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) MELALUI KEGIATAN WORKSHOP DI TK KECAMATAN SUNGAI LALAK - Rinawati Rinawati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the still weak ability of teachers in the use of information and communication technology (ICT). This research was conducted in all kindergarten assisted by researchers in the Lalak River District. Sabjek of this study were all kindergarten teachers in the District of Sungai Lalak which numbered 25 teachers. The purpose of this study is to improve the ability of teachers to use information and communication technology (ICT) through workshop activities. This research consists of two cycles, each of which consists of 4 stages, namely, planning, implementation, observation, and reflection. The results of the study prove that in the first and second cycles, it can be seen that the competence in the use of information and communication technology (ICT) in TK Lalak District Kindergarten teachers is generally in the medium category. In the first aspect of the first cycle, 4 people or 16% kindergarten teachers have a high ability regarding the use of information and communication technology (ICT), while the second cycle increases to 10 people or 40%. In the second category there were 14 people or 56% who had moderate abilities regarding the use of ICTs, while the second cycle had 12 people or 48% who had moderate abilities. In the third aspect of the first cycle of 7 people or 28% have not been able to master the use of ICT, while in the second cycle reduced to 3 people or 12% have not been able to master the use of information and communication technology (ICT). Based on the description that has been described, the researcher draws conclusions from the results of research conducted that the implementation of information and communication technology (ICT) workshops can improve the ability of teachers in the use of information and communication technology (ICT) in TK Lalak River District.